Current induced magnetization switching in Pt/Co/Cr structures with enhanced perpendicular magnetic anisotropy and spin Hall effect. (19th March 2019) - Cui, Baoshan; Yun, Jijun; Yang, Kunya; Wu, Hao; Zhu, Zhendong; Zuo, Yalu; Yang, Dezheng; Gao, Meizhen; Zhang, Zongzhi; Xi, Li; Wang, Kang L.
Abstract: We study the perpendicular magnetic anisotropy (PMA) and spin–orbit torques (SOTs) in Pt/Co/Cr stacks as a function of Cr thickness. An enhanced PMA is observed and ascribed to the strong interfacial anisotropy between Co and Cr. Moreover, SOTs induced magnetization switching is achieved under relatively small critical current density in the order of 10 6 A cm −2 due to the enhanced effective spin Hall angle ( θ S H e f f ) up to 0.15–0.27. Significantly, the linear dependence between θ S H e f f and the square of longitudinal resistivity suggests that the spin Hall effect may arise from the intrinsic mechanism in our systems.